Old Yellow Enzyme from Trypanosoma cruzi Exhibits In Vivo Prostaglandin F2α Synthase Activity and Has a Key Role in Parasite Infection and Drug Susceptibility - Díaz-Viraqué, Florencia; Chiribao, María Laura; Trochine, Andrea; González-Herrera, Fabiola; Castillo, Christian; Liempi, Ana; Kemmerling, Ulrike; Maya, Juan Diego; Robello, Carlos (Frontiers in Immunology, 2018)
The discovery that trypanosomatids, unicellular organisms of the order Kinetoplastida, are capable of synthesizing prostaglandins raised questions about the role of these molecules during parasitic infections. Multiple studies indicate that prostaglandins could be related to the infection processes and pathogenesis in trypanosomatids. This work aimed to unveil the role of the prostaglandin F2α synthase TcOYE in the establishment of Trypanosoma cruzi infection, the causative agent of Chagas disease. This chronic diseases affects several million people in Latin America causing high morbidity and mortality. Here we propose a prokaryotic evolutionary origin for TcOYE, and then we used in vitro and in vivo experiments to show that T. cruzi prostaglandin F2α synthase has an important role modulating the infection process. TcOYE overexpressing parasites were less able to complete the infective cycle in cell culture infections and increased cardiac tissue parasitic load in infected mice. Additionally, parasites overexpressing the enzyme increased PGF2α synthesis from arachidonic acid. Finally, an increase in Benznidazole and Nifurtimox susceptibility in TcOYE overexpressing parasites showed its participation in activating the currently anti-chagasic drugs, which added to its observed ability to confer resistance to hydrogen peroxide, highlights the relevance of this enzyme in multiple events including host-parasite interaction.